THE REPRESENTATION OF URBAN SPACE IN CORRELATION WITH THE MOTIVE OF THE NEWCOMER WITH THE GRADATION OF ADAPTABILITY IN USKOKOVIC'S WORK (Heritage, 2025)
The work examines the city from a slanted perspective, through psychological experience and social, societal, cultural and educational interaction between space and newcomers. By dynamizing Belgrade, noticing elements of the phenomenology of imagination and folklore code, the degree of integration of newcomers into the new environment is expressed, as well as the perception of the mental representation of the homeland and, in this regard, the shaping of psychological space and adaptation in relation to the domicile population. Using an analytical method and a comparative approach, Belgrade-Homeland analyzes and deepens the formation of the social representation of the city in the process of innovation and epochal changes (oriental town, city in the modern sense) and the intertwining of the individual identities of Milos and Zorka with the collective interpenetration of newcomers and Belgraders. The goal of the research is to detect in all domains of everyday life the intertwining of newcomer motives and the urban environment, as well as the manifestation of the psychological process of modifying personal identity in response to changed life circumstances.
Keywords: Milutin Uskokovic, Newcomers, Belgrade, newcomer motif, personal and collective identity.